1980
DOI: 10.1002/1097-0142(19800101)45:1<51::aid-cncr2820450110>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Breast thermography and cancer risk prediction

Abstract: Thermography makes a significant contribution to the evaluation of patients suspected of having breast cancer. The obviously abnormal thermogram carries with it a high risk of cancer. This report summarizes the results of patients with questionable or stage Th III thermograms. From approximately 58,000 patients, most of whom had breast complaints, examined between August 1965 and June 1977, the conditions or a group of 1,245 women were diagnosed at initial examination as either normal or benign disease by conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(49 citation statements)
references
References 3 publications
2
46
0
1
Order By: Relevance
“…Characteristically, temperatures levelled off after three-quarters of an hour and the computer-identified crest was taken as the temperature for that day. These measurements are in contrast to classical infrared thermometry (Gautherie and Gross, 1980), which defines a surface distribution of temperature, i.e. the venous architecture.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Characteristically, temperatures levelled off after three-quarters of an hour and the computer-identified crest was taken as the temperature for that day. These measurements are in contrast to classical infrared thermometry (Gautherie and Gross, 1980), which defines a surface distribution of temperature, i.e. the venous architecture.…”
Section: Methodsmentioning
confidence: 93%
“…First, epidemiologists have reported that there is a transient increase in breast cancer in the post partum after the physiological hypervascularity of pregnancy (Chie et al, 2000). Second, infra-red thermographers have reported that 38% of 784 breast clinic patients with asymmetric focal or global 'hyperthermia' of the breasts at initial examination developed 'clinical' cancer some years later (Gautherie and Gross, 1980). Third, we have reported (Simpson et al, 1995) Figure 5 Same data as Figure 1 but in this case the data are partitioned by whether the subject had had a longer than average or shorter than average (11.2 years) pregnancy-free interval prior to the Chronobra study.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study of 58,000 women being screened for breast cancer, there were 784 patients that had an abnormal asymmetric IR image of their breasts, 298 (38%) of these 784 patients were diagnosed with breast cancer within four years. 2 IR technology has shown great potential for differentiating a second-degree burn from a third-degree burn. 3 Many burn patients for whom the physician cannot initially determine whether the burn is a second-or third-degree burn have to wait 5 to 7 days before a decision.…”
Section: Examples Of Infrared Imaging Technologies For Tissue Imagingmentioning
confidence: 99%
“…The malignant part is clearly visible in Figure 4b. Studies have shown a high correlation between obviously abnormal thermograms and increased breast cancer risk as well as a poorer prognosis for the breast cancer patient [14,16]. A constant irregular thermogram carries a 22 times higher risk than its regular counterpart and it is 10 times more indicative than a first-order family history of the illness as a future risk signal for breast cancer.…”
Section: Breast Cancermentioning
confidence: 99%
“…To be specific, only five out of 27 participating cancer centers had sufficiently qualified personal for taking and assessing thermography images. Gautherie et al pointed out that a lack of technical skill and expertise for thermography image interpretation leads to a sharp decline in diagnostic accuracy [16]. The need for quality assurance, during the act of image acquisition, is further emphasized by the fact that the high false positive range of 10-30% depends on the disease and the technique used.…”
mentioning
confidence: 99%